2017
DOI: 10.1016/j.epsl.2016.12.033
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic exploration of a low-temperature ultramafic-hosted hydrothermal site (Lost City, 30°N, MAR)

Abstract: 25A 2003 high-resolution magnetic survey conducted by the Autonomous Underwater Vehicle ABE 26 over the low-temperature, ultramafic-hosted hydrothermal field Lost City reveals a weak positive 27 magnetic anomaly. This observation is in direct contrast to recent observations of strong positive 28 magnetic anomalies documented over the high-temperature ultramafic-hosted hydrothermal vents 29 fields Rainbow and Ashadze, which indicates that temperature may control the production of 30 magnetization at these sites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
0
7
1
Order By: Relevance
“…The positive magnetic anomaly observed over UMHSs results from several factors, including (1) an accumulation of strongly magnetized magnetite produced by serpentinization reactions within the hydrothermal plumbing and stockwork zones; (2) the dimensions of the hydrothermal system at depth, i.e., the volume of its deep parts; and (3) the presence of reducing hydrothermal fluids that prevent later oxidation of serpentinitehosted magnetite by contact with seawater (Szitkar et al, 2014b). In addition, it has also been shown that the amount of magnetite produced by serpentinization reactions is influenced by hydrothermal fluid temperature (Szitkar et al, 2017), in accordance with laboratory experiments (Klein et al, 2014). Indeed, high temperatures (>200 °C) favor iron partitioning into magnetite, whereas low temperatures preferentially partition it into less-magnetic brucite (Früh-Green et al, 1996, 2004Klein et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The positive magnetic anomaly observed over UMHSs results from several factors, including (1) an accumulation of strongly magnetized magnetite produced by serpentinization reactions within the hydrothermal plumbing and stockwork zones; (2) the dimensions of the hydrothermal system at depth, i.e., the volume of its deep parts; and (3) the presence of reducing hydrothermal fluids that prevent later oxidation of serpentinitehosted magnetite by contact with seawater (Szitkar et al, 2014b). In addition, it has also been shown that the amount of magnetite produced by serpentinization reactions is influenced by hydrothermal fluid temperature (Szitkar et al, 2017), in accordance with laboratory experiments (Klein et al, 2014). Indeed, high temperatures (>200 °C) favor iron partitioning into magnetite, whereas low temperatures preferentially partition it into less-magnetic brucite (Früh-Green et al, 1996, 2004Klein et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, high temperatures (>200 °C) favor iron partitioning into magnetite, whereas low temperatures preferentially partition it into less-magnetic brucite (Früh-Green et al, 1996, 2004Klein et al, 2014). This latter case is likely to result in the formation of a limited amount of magnetite within the stockwork zones beneath UMHSs, and hence a weak positive magnetic anomaly (Szitkar et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations